Towards an integrated framework for evaluating transformative innovation policy - Haddad, Carolina R.; Bergek, Anna (Research Policy, 2023)
In recent years, a new frame for innovation policy has emerged, namely “transformative innovation policy” (TIP), which aims at addressing transformative change or “Grand Challenges”. Such a shift in policy theory should, ideally, be reflected in policy evaluation, but the literature has so far provided little advice on how to address TIP-related evaluation challenges such as directionality and system-level behavioural additionality. This paper discusses how the evaluation of policy interventions targeting system innovation can be designed to address these challenges. Combining the literature on sustainability transitions with policy evaluation, we propose an integrated evaluation framework composed of three main components: (i) programme theory (programme goals, systems boundaries and desired (or accepted) development paths); (ii) system analysis (transformative outcomes); and (iii) synthesis and overall assessment (including revision of programme theory). By integrating the two sets of literature, we provide a bridge between academic research on transitions and current evaluation practices. We briefly illustrate the applicability of the integrated framework in the BioInnovation Strategic Innovation Programme in Sweden.